2017
DOI: 10.1002/1873-3468.12544
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of BC200 RNA‐mediated translation inhibition by hnRNP E1 and E2

Abstract: The long noncoding RNA BC200 (brain cytoplasmic RNA, 200 nucleotides) acts as a translational modulator of local protein synthesis at dendrites. BC200 RNA has been shown to inhibit translation in vitro, but it remains unknown how this translation inhibition might be controlled in a cell. Here, we performed yeast three-hybrid screening and identified hnRNP E1 and hnRNP E2 as BC200 RNA-interacting proteins. We found that: these hnRNA proteins could restore BC200 RNA-inhibited translation; BC200 RNA interacts wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…We recently identified a heterogeneous ribonucleoprotein E2 (hnRNP E2, also known as PCBP2) as a BC200 RNA-interacting protein (13). hnRNP E2 binds to BC200 RNA mainly through the unique 3′ C-rich domain (nts 162-200) of BC200 RNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently identified a heterogeneous ribonucleoprotein E2 (hnRNP E2, also known as PCBP2) as a BC200 RNA-interacting protein (13). hnRNP E2 binds to BC200 RNA mainly through the unique 3′ C-rich domain (nts 162-200) of BC200 RNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…BC200 RNA is known to be targeted to dendrites by hnRNP A2/B1 in neuronal cells (19). Likewise, it is likely that BC200 RNA could be targeted to p-bodies by hnRNP E2 in HeLa cells because the p-body constituent (hnRNP E2) is a binding partner of BC200 RNA (13). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this latter context, it has been suggested that other BC200 RNA-binding proteins can hinder protein binding to a specific BC200 RNA motif (12). Notably, it has also been reported that hnRNP E1 and E2 restore BC200 RNA-inhibited translation by binding the C-rich domain (32). Therefore, it is possible that individual RNA motifs may be differently involved in BC 200 RNA-mediated translational regulation in a cell-type-specific and spatially distinct manner.…”
Section: Discussionmentioning
confidence: 99%
“…Other work has demonstrated a higher affinity of hnRNP E1 for hnRNP D than hnRNP E2 [17], and hnRNP E1 and hnRNP E2 have differential responses to hypoxic stress [39]. Both hnRNP E1 and hnRNP E2 can regulate BC200 RNA-mediated translation inhibition but not through the same control mechanism [16]. Therefore, despite the high degree of sequence similarities between hnRNP E1 and hnRNP E2 isoforms, they each have distinct non-redundant cellular functions.…”
Section: Discussionmentioning
confidence: 99%